When diets fall short: link between unsuccessful weight loss and reduced BDNF levels - Wu, Gang; Shi, Guifeng; Ye, Yafei; He, Xiaoqin; Chen, Yahong; Liu, Cuimin; Zhang, Meixian (Frontiers in Nutrition, 2025)
ObjectivesBrain-derived neurotrophic factor (BDNF) is a protein essential for brain health and nutrient energy metabolism. This study aims to examine the relationship between blood BDNF levels and obesity and to assess the effect of energy-restricted diets on BDNF levels.MethodWe enrolled 233 individuals with normal weight (n = 102), overweight (n = 52), and obesity (n = 69) and measured their serum BDNF levels. Totally 49 overweight and obese participants then followed a 4-week energy-restricted diet. Paired tests were used to statistically evaluate changes in serum BDNF levels before and after the diet. Based on the effectiveness of weight loss, participants were divided into high- and low-response groups. Changes in BDNF levels before and after the diet were further analyzed separately in the high- and low-response groups for both men and women.ResultsOur findings showed that serum BDNF levels were significantly elevated in overweight and obese adults in the Chinese population studied (P = 0.002). Energy restriction led to a significant decrease in BDNF levels in overweight and obese participants (before: 19,605.13 ± 5,706.07 pg/ml, after: 16,437.39 ± 5,365.13 pg/ml, P < 0.001). In subgroup analysis, a reduction in BDNF levels was observed only in the female hyporesponsive group (P = 0.001).ConclusionSerum BDNF levels were elevated in overweight and obese adults in the Chinese population, and an energy-restricted diet reduced serum BDNF. In women, failure to achieve weight loss with an energy-restricted diet may be associated with decreased BDNF levels. Maintaining stable BDNF levels, such as through exercise, should be considered to enhance weight loss outcomes. Confounding factors such as the menstrual cycle, menopausal status, and levels of physical activity should be taken into consideration in future studies.